FLOATATION — SPECTROPHOTOMETRIC DETERMINATION OF PHOSPHORUS AS BRILLIANT GREEN-MOLYBDOPHOSPHATE ION-PAIR - Niazi, Shahida B.; Naz, Sahar (Journal of Research (Science), 1993)
Orthophosphate in natural waters is determined spectrophotometrically as Brilliant Green–Molybdophosphate ion-pair. The ion-pair is floated as a membrane-like substance at the interface between the aqueous and diethyl ether phases. After discarding the aqueous phase, the excess of Brilliant Green extracted into the diethyl ether along with the ion-pair is removed by shaking with 25 ml of 1.0 M hydrochloric acid. The floated ion-pair is dissolved in methanol and absorbance is measured at 625 nm against methanol. The calibration graph is linear upto 1 μg with a relative standard deviation of 3.2% at 0.3 μg phosphate phosphorus. The detection limit is 2.5 μg l⁻¹ which is twice of the standard deviation of the reagent blank. The apparent molar absorptivity for orthophosphate phosphorus is 1.25 × 10⁴ l mol⁻¹ cm⁻¹. Arsenic (V), citrate, tartrate and sulphate interfere.